(untitled) (Journal of Comparative Social Work, 2017)
The transformative reality of diverse Canadian families is outpacing national and provincial statutes and policies. Social workers in child welfare agencies are faced with the complex task of making decisions about families while working within the confines of national/provincial statutes and social policies, as well as within agency structures. They attempt to balance the rights of diverse Canadian families and still protect children at risk of harm with the principle of the ‘best interest of the child’. The purpose of this qualitative case study was to explore the construction of ‘family’ and decisions about family life in protection services from the perspective of professional social workers in the prairie region of Canada. Social workers from several urban communities were invited to participate in focus groups. During the focus group discussions, themes of social worker’s nuanced and somewhat fluid understandings of family did not always converge with current legal and professional notions of families. Study findings suggest that social workers’ construction of family and the decisions they make about family life involve three primary themes: ‘acceptance of diverse understandings of family’; ‘safety and the best interest of the child’, and ‘professional discretionary decisions’